2005
DOI: 10.1002/mnfr.200500054
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of conjugated linoleic acid in total and subcellular fractions from normal and cancerous parts of human testes

Abstract: The objective of the present study was to examine differences in the fatty acid composition of subcellular fractions from normal and cancerous parts of human testes. The conjugated linoleic acid (CLA) content was significantly higher in total testicular carcinoma (TC), but significantly lower in the mitochondrial fraction of TC in comparison to normal testicular tissue. The subcellular distribution pattern of CLA was similar to that of monounsaturated fatty acids, but different to that of 18:2n-6 (linoleic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…So far, few studies have been published to explain whether conjugated linoleic acid isomers may modify the activity of lipoxygenases (15-LO and 5-LO) in cells. Results showed by Hoffmann indicate that CLAs change availability of substrates (mainly arachidonic acid) for the lipoxygenase pathways generating eicosanoids (39), partly by inhibition of the phospholipase A 2 activity (40). CLA may also change content of lipoxygenases in the cells.…”
Section: Discussionmentioning
confidence: 99%
“…So far, few studies have been published to explain whether conjugated linoleic acid isomers may modify the activity of lipoxygenases (15-LO and 5-LO) in cells. Results showed by Hoffmann indicate that CLAs change availability of substrates (mainly arachidonic acid) for the lipoxygenase pathways generating eicosanoids (39), partly by inhibition of the phospholipase A 2 activity (40). CLA may also change content of lipoxygenases in the cells.…”
Section: Discussionmentioning
confidence: 99%
“…The lover levels of C17:1, C18:0, C18:2 n-6, C20:4 n-6 were observed in serum and microsomes of DMBA-treated groups, whereas C18:2 n-6 and C18:3 n-3 showed the opposite tendency. Hoffmann et al also observed differences between fatty acids profile of healthy and cancerous tissues, especially the n-3 and n-6 fatty acids content [27,28]. …”
Section: Resultsmentioning
confidence: 99%
“…This observation is in disagreement with the results of Hoffmann et al, who found CLA content to be significantly higher in total cancerous testicular tissue than in normal. Only in mitochondrial fraction of cancerous tissue CLA concentration tended to be lower than in normal tissue, whereas other subcellular fractions showed the opposite tendency [28]. …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, other studies carried out in women with breast cancer, invasive breast carcinoma or benign breast disease failed to reveal any positive correlation between CLA and incidence of cancer [70,71]. Nevertheless, it has to be mentioned that analysis of subcellular fractions from normal and cancerous parts of human tests revealed that CLA content was significantly higher in testicular carcinoma, but low in the mitochondrial fraction of this tumor in comparison with normal tissue [72].…”
Section: Dairy Fas and Cancermentioning
confidence: 92%